Нові підходи до збереження та використання природних комплексів ботанічного заказника Гектова балка" у Донбасі - Приходько, С.А.; Шевчук, О.М.; Остапко, В.М. (Промышленная ботаника, 2002)
The results of a detailed geobotanic and floristic examination of the “Hectova balka” botanic nature reserve (Dobropolsky district, Donetsk region) established with a purpose of preserving the typical floral complex and vegetation of mixed grassesfescue-feather-grass steppes are adduced. A new approach to making efficient use of its vegetation cover is considered, that consists in laying out of the ecological path with the scientific, nature-conservation, education, recreational functions.